2020
DOI: 10.5812/numonthly.99178
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Link Between Saphenofemoral Insufficiency and Varicocele: Imaging Study of Sub-Fertile Men

Abstract: Background:Varicocele is an important cause of infertility in men. Some studies have suggested that because of the similar pathologic processes involved in chronic venous diseases and varicocele, saphenofemoral insufficiency is an example of chronic venous disease, which causes varicose veins in the lower extremity. It is thought that there may be a relation between saphenofemoral abnormality and the emergence of varicocele, but this relation is not backed by sufficient evidence. Methods: In this prospective d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Five of the seven included case-control studies reported the risk of saphenofemoral insufficiency in the varicocele and control groups. 6,[8][9][10]13 In four studies, saphenofemoral insufficiency was defined as femoral saphenous reflux time greater than 0.5 s. In one remaining study, femoral saphenous reflux was defined as retrograde flow of more than 1 s. Ultimately, 872 cases were included, with 482 cases in the varicocele group and 390 cases in the control group. The pooled analysis indicated that the risk of saphenofemoral insufficiency in the varicocele group was higher than that in the control group (OR: 2.80; 95% CI: 2.03, 3.84; p < 0.00001; Figure 4), and low heterogeneity in the pooled effect estimates was found (p = 0.32; I 2 = 14%; Figure 4).…”
Section: Saphenofemoral Insufficiencymentioning
confidence: 99%
“…Five of the seven included case-control studies reported the risk of saphenofemoral insufficiency in the varicocele and control groups. 6,[8][9][10]13 In four studies, saphenofemoral insufficiency was defined as femoral saphenous reflux time greater than 0.5 s. In one remaining study, femoral saphenous reflux was defined as retrograde flow of more than 1 s. Ultimately, 872 cases were included, with 482 cases in the varicocele group and 390 cases in the control group. The pooled analysis indicated that the risk of saphenofemoral insufficiency in the varicocele group was higher than that in the control group (OR: 2.80; 95% CI: 2.03, 3.84; p < 0.00001; Figure 4), and low heterogeneity in the pooled effect estimates was found (p = 0.32; I 2 = 14%; Figure 4).…”
Section: Saphenofemoral Insufficiencymentioning
confidence: 99%